Lianhuaqingwen capsule inhibits influenza-induced bacterial adhesion to respiratory epithelial cells through down-regulation of cell adhesion molecules. (15th November 2021) - Du, Qiuling; Huang, Wenbo; Zhao, Jin; Zeng, Jun; Zhang, Wenjie; Huang, Xiaodong; Chen, Ruifeng; Jiang, Haiming; Xie, Yuqi; Wang, Yutao; Zhong, Nanshan; Wang, Xinhua; et al.
Abstract: Ethnopharmacological relevance: Influenza virus infection is widely believed to cause mild symptoms, but can lead to high mortality and severe disease complicated by secondary bacterial pneumonia. Traditional Chinese medicine (TCM) has been proposed as a promising agent to treat respiratory viral infections. A herbal formula Lianhuaqingwen capsule (LHQW) comprising two prescriptions: Maxing Shigan decoction and Yinqiao San, has been used clinically to treat respiratory infection with immune regulatory effects. However, little is known about the capacity of LHQW against influenza-induced secondary bacterial pneumonia. Aim of study: This study aimed to evaluate the efficacy and underlying mechanism of LHQW on influenza A virus A/PR/8/34 (PR8) secondary methicillin-resistant Staphy-lococcus aureus (MRSA) infection. Methods: The anti-adhesion activity of LHQW against PR8-induced MRSA infection was assessed in human lung epithelial (A549) cells and the effect of LHQW on the expression of intracellular adhesion molecule 1 (ICAM-1) was detected. Also, the mRNA expression levels of inflammatory cytokines upon lipopolysaccharide (LPS) stimulation in PR8-infected A549 cells were determined. The body weight change, survivals, viral titers, colonies and the pathological parameters after LHQW treatment in severe pneumonia model have all been systematically determined. Results: LHQW significantly reduced the adhesion of MRSA to PR8-infected A549 cells in a dose-dependent manner by suppressing the up-regulation of bacterial receptors. LHQW also markedly declined the overexpression of IL-6, IL-8, and TNF-α induced by LPS stimulated-A549 cells following influenza virus infection. Furthermore, the abnormal changes of lung index in dual-infection mice were relieved after administered with LHQW in preventive and therapeutic mode, but with no significantly difference ( P > 0.05). LHQW could not effectively improve survival rate or prolong the survival time of mice ( P > 0.05). LHQW (1000 mg/kg/d) administered prophylactically significantly decreased the lung viral titers ( P < 0.05), slightly downregulated IL-6 but TNF-α, IL-1β levels and improved lung pathological inflammation including neutrophil infiltration, necrosis, which is consistent with the expression of inflammatory factors. Conclusions: LHQW inhibited influenza-induced bacterial adhesion by down-regulating the adhesion molecules with the improvement trend on severe pneumonia, indicating that it can be used as an adjuvant medication in severe viral-bacterial pneumonia therapy rather than as a single medication. Graphical abstract: Image 1